Mediated orthodoxy: Salafi thought and student piety at Universitas Sriwijaya - Afandi, Muhamad Ridwan; Rizqullah, Muhammad Naufan; Arifin, Jafar (Geuthèë Institute, Aceh, 2025)
This study examines how Salafi religiosity is transformed and negotiated among university students at Universitas Sriwijaya (UNSRI), South Sumatra, within a pluralistic academic environment and an expanding digital ecosystem. Employing a qualitative ethnographic approach combined with digital observation, the research explores how students interpret manhaj salaf and enact piety in everyday campus life. Data were collected through participant observation, semi-structured interviews with students, lecturers, and alumni, as well as analysis of Islamic content circulated on Instagram and Telegram. The findings reveal that Salafi piety at UNSRI functions both as a moral discipline and a social boundary, manifested through selective knowledge practices, modest dress, and gender segregation. Digital platforms play a central role in mediating religious authority, enabling students to reproduce scriptural norms through visual and networked forms of da’wah. At the same time, digital engagement tends to reinforce ideological homogeneity and promote Arabized aesthetics as markers of religious authenticity. Although Salafi students generally maintain apolitical orientations, their presence subtly shapes moral norms and everyday conduct on campus. The study contributes to discussions on digital religion and mediated orthodoxy by demonstrating how Salafi communities adapt purist ideals to modern institutional and technological contexts. Practically, the findings highlight the need for inclusive university policies that accommodate conservative piety while sustaining civic pluralism.